Does topical tranexamic acid reduce postcoronary artery bypass graft bleeding? - Amir Mirmohammadsadeghi; Mohsen Mirmohammadsadeghi; Mahnaz Kheiri (Journal of Research in Medical Sciences, 2018)
Background: Postoperative bleeding is a common problem in cardiac surgery. We tried to evaluate the effect of topical tranexamic acid (TA) on reducing postoperative bleeding of patients undergoing on-pump coronary artery bypass graft (CABG) surgery. Materials and Methods: One hundred and twenty-six isolated primary CABG patients were included in this clinical trial. They were divided blindly into two groups; Group 1, patients receiving 1 g TA diluted in 100 ml normal saline poured into mediastinal cavity before closing the chest and Group 2, patients receiving 100 ml normal saline at the end of operation. First 24 and 48 h chest tube drainage, hemoglobin decrease and packed RBC transfusion needs were compared. Results: Both groups were the same in baseline characteristics including gender, age, body mass index, ejection fraction, clamp time, bypass time, and operation length. During the first 24 h postoperatively, mean chest tube drainage in intervention group was 567 ml compared to 564 ml in control group (P = 0.89). Mean total chest tube drainage was 780 ml in intervention group and 715 ml in control group (P = 0.27). There was no significant difference in both mean hemoglobin decrease (P = 0.26) and packed RBC transfusion (P = 0.7). Topical application of 1 g TA diluted in 100 ml normal saline does not reduce postoperative bleeding of isolated on-pump CABG surgery. Conclusion: We do not recommend topical usage of 1 g TA diluted in 100 ml normal saline for decreasing blood loss in on-pump CABG patients.